2006
DOI: 10.1086/504358
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Tuberculosis Infection Using Whole-Blood Interferon-γ and Mantoux Testing Among Japanese Healthcare Workers

Abstract: Positive QFT-G results were closely associated with the presence of risk factors for LTBI in a hospital setting, suggesting that the QFT-G can detect LTBI in a population composed predominantly of BCG vaccinees. Because most HCWs worldwide have been vaccinated with BCG, the QFT-G offers a significant improvement over the TST in tuberculosis screening programs and minimizes unwarranted use of tuberculosis prophylaxis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
76
5
4

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(104 citation statements)
references
References 22 publications
19
76
5
4
Order By: Relevance
“…The results of the present study were matching with Harada et al (2006) who compared the performance of TST and Quantiferon in a total of 304 HCWs. They found that concordant results were lower than discordant results (14 and 86%, respectively).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The results of the present study were matching with Harada et al (2006) who compared the performance of TST and Quantiferon in a total of 304 HCWs. They found that concordant results were lower than discordant results (14 and 86%, respectively).…”
Section: Discussionsupporting
confidence: 78%
“…The rate of detection of LTBI assessed by QFT-GIT in our study was 36%. Low detection rates by QFT-GIT as compared to TST were also reported by other scientists: Harada et al (2006), Soborg et al (2007), Niehaus et al(2008a), Stebler et al (2008) and Ringshausen et al, (2009).…”
Section: Discussionsupporting
confidence: 69%
“…Although it is difficult for us to determine whether the specificity of two IGRAs in the diagnosis of LTBI is appropriate since there is no gold standard for LTBI, Harada et al reported that the positive rate of the IGRA was 3.1% for comparatively-young Japanese healthcare workerssimilar to our subjects [3]. With reference to this, the specificity of two IGRAs seemed reasonable in our study.…”
Section: Discussionsupporting
confidence: 57%
“…Routine TB screening for HCW is considered as a cornerstone for preventing TB in hospitals and it is performed in many highincome countries, for example, USA [9], Japan [21], France [22], Spain [23] and Switzerland [24]. In the UK, TB screening of HCW is mainly performed as a pre-employment screening [25].…”
Section: Tb Screening For Hcwmentioning
confidence: 99%
“…The difference in Review the prevalence of positive TST and IGRA was not statistically significant in seven studies [25,48,[53][54][55][56][57]. In the other 24 studies, the difference was statistically significant [13,21,23,27,30,46,47,[49][50][51][58][59][60][61][62][63][64][65][66][67][68][69][70]. However, there was no clear trend that TST-positive/ IGRA-negative discordant results increased with an increasing proportion of BCG-vaccinated HCW in the study populations.…”
Section: The Effect Of Introducing Igra In Tb Screening Of Hcwmentioning
confidence: 99%